2013
DOI: 10.1097/adm.0b013e31828a0265
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality-Based Recovery From Drug Addiction in the Twelve-Step Fellowship of Narcotics Anonymous

Abstract: Spiritual renewal combined with an abstinence-oriented regimen in Narcotics Anonymous social context can play a role in long-term recovery from drug addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…While the nuances of the Sikh model exist, parallels can be noted with other religious frameworks of change, highlighted in this special edition and put forward by other theorists. There are, for example, a growing number of spirituality-based "Twelve Step" informed pathways to sobriety such as Narcotics Anonymous [30] and "Free N-One", a drug and alcohol Black Christian support group in the U.S. [31]. These pathways, however, are not limited to the 12-step process, as shown in the Sikh spiritual framework; there are also through groups such as Women for Sobriety [32], characterized by a 13-statement "New Life" program for change.…”
Section: Discussionmentioning
confidence: 99%
“…While the nuances of the Sikh model exist, parallels can be noted with other religious frameworks of change, highlighted in this special edition and put forward by other theorists. There are, for example, a growing number of spirituality-based "Twelve Step" informed pathways to sobriety such as Narcotics Anonymous [30] and "Free N-One", a drug and alcohol Black Christian support group in the U.S. [31]. These pathways, however, are not limited to the 12-step process, as shown in the Sikh spiritual framework; there are also through groups such as Women for Sobriety [32], characterized by a 13-statement "New Life" program for change.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been a focus in the peer-reviewed literature. [1][2][3][4][5][6] We have reported previously on the role of Narcotics Anonymous (NA) in addiction recovery 7,8 and on the relatively small portion of attendees (35%) at NA meetings who were referred to NA by professionals; 7 this suggests that there may be a population of veterans whose substance use and PTSD were addressed in the fellowship of NA and not necessarily through professional referral. An evaluation of community-based veterans' use of NA for symptom relief may, therefore, provide useful information on a way of enhancing existing treatment programs.…”
Section: Introductionmentioning
confidence: 95%
“…This is evident even in studies of the value of interpersonal support in mitigating such symptoms. [8][9][10] In light of this, we solicited Narcotics Anonymous World Services to cooperate in accessing NA groups across the United States that NA staff knew might have at least some members who were veterans, thereby allowing for evaluating veteran and non-veteran members who participated together in the fellowship.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Scott A. Teitelbaum in his book "Addiction: A family Affair (2011) since there is no known "cure" for addiction, it is imperative that prevention must start with the family. Finally Galanter et al [85] reported that patients more oriented toward a spiritual than a formerly religious affiliation toward other 12-step members (a spiritual awakening) associated with lower rates of substance seeking behavior. Evidence continues to emerge regarding our understanding of brain function especially the reward circuitry and all addictive behaviors and clinicians are encouraged to review some of the select molecular neurogenetic literature [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: Beyound Vaillantmentioning
confidence: 99%